Alternative life‐history strategy contributions to effective population size in a naturally spawning salmon population - Erika King; Megan V. McPhee; Scott C. Vulstek; Curry J. Cunningham; Joshua R. Russell; David A. Tallmon (Evolutionary Applications, 2023)
Abstract Alternative life‐history tactics are predicted to affect within‐population genetic processes but have received little attention. For example, the impact of precocious males on effective population size (Ne) has not been quantified directly in Pacific salmon Oncorhynchus spp., even though they can make up a large percentage of the total male spawners. We investigated the contribution of precocial males (“jacks”) to Ne in a naturally spawning population of Coho Salmon O. kisutch from the Auke Creek watershed in Juneau, Alaska. Mature adults that returned from 2009 to 2019 (~8000 individuals) were genotyped at 259 single‐nucleotide polymorphism (SNP) loci for parentage analysis. We used demographic and genetic methods to estimate the effective number of breeders per year (Nb). Jack contribution to Nb was assessed by comparing values of Nb calculated with and without jacks and their offspring. Over a range of Nb values (108–406), the average jack contribution to Nb from 2009 to 2015 was 12.9% (SE = 3.8%). Jacks consistently made up over 20% of the total male spawners. The presence of jacks did not seem to influence Nb/N. The linkage disequilibrium Ne estimate was lower than the demographic estimate, possibly due to immigration effects on population genetic processes: based on external marks and parentage data, we estimated that immigrant spawners produced 4.5% of all returning offspring. Our results demonstrate that jacks can influence Nb and Ne and can make a substantial contribution to population dynamics and conservation of threatened stocks.